MICROBIAL COMMUNITY OF BLACK BAND DISEASE ON INFECTION, HEALTHY, AND DEAD PART OF SCLERACTINIAN Montipora sp. COLONY AT SERIBU ISLANDS, INDONESIA - Ofri Johan; Dietriech Geoffrey Bengen; Neviaty Putri Zamani; Suharsono Suharsono; David Smith; Angela Mariana Lusiastuti; Michael Sweet (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
It is crucial to understand the microbial community associated with the host when attempting to discern the pathogen responsible for disease outbreaks in scleractinian corals. This study determines changes in the bacterial community associated with Montipora sp. in response to black band disease in Indonesian waters. Healthy, diseased, and dead Montipora sp. (n = 3 for each sample type per location) were collected from three different locations (Pari Island, Pramuka Island, and Peteloran Island). DGGE (Denaturing Gradient Gel Electrophoresis) was carried out to identify the bacterial community associated with each sample type and histological analysis was conducted to identify pathogens associated with specific tissues. Various Desulfovibrio species were found as novelty to be associated with infection samples, including Desulfovibrio desulfuricans, Desulfovibrio magneticus, and Desulfovibrio gigas, Bacillus benzoevorans, Bacillus farraginis in genus which previously associated with pathogenicity in corals. Various bacterial species associated with uninfected corals were lost in diseased and dead samples. Unlike healthy samples, coral tissues such as the epidermis, endodermis, zooxanthellae were not present on dead samples under histological observation. Liberated zooxanthellae and cyanobacteria were found in black band diseased Montipora sp. samples.